Analisis Implementasi Sistem Pengendalian Internal Pemerintah (SPIP) dalam Pengelolaan Anggaran Keuangan Daerah - Fitri Angraini; Sindi Rahayu; Desinta Bella Irwana (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
Local government budget management is a crucial element in regional governance, as it directly impacts accountability, transparency, and efficiency in public service delivery. To support effective regional financial management, the Indonesian Government has established the Government Internal Control System (SPIP), as stipulated in Government Regulation Number 60 of 2008. This study aims to examine the role and practical implementation of SPIP in regional budget management through a case study of the Regional Financial and Asset Management Agency (BPKAD) of Dumai City. Using a qualitative case study approach, this study analyzes regional financial documents, audit reports from the Regional Audit Agency (BPKAD), as well as laws and regulations and internal policies governing SPIP implementation. The results indicate that SPIP has been implemented in BPKAD Dumai City throughout the budget management cycle, from planning and implementation to reporting and accountability. However, its implementation has not reached an optimal level due to constraints such as limited leadership commitment, inadequate human resource capacity, and suboptimal internal oversight mechanisms. Therefore, improving SPIP implementation is a strategic step to realize accountable, transparent, and performance-oriented regional financial governance.